Ebb and Flow Balanchine at the Coliseum and Covent Garden - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Balanchine at the Coliseum and Covent Garden: Serenade, Agon and Symphony in C